State-Dependent Risk Aversion - Pascal St. Amour (Queen's University, Department of Economics, 1994)
The traditional representative agent, consumption-based asset pricing model with iso-elastic utility has not performed well empirically. Alternative specifications have focused on the rigidities implied by the Von Neuman-Morgenstern axioms of choice under uncertainty, in particular the independence hypothesis, and proposed some degree of generalization. This has been achieved while retaining constant risk aversion for the within-period utility function. The purpose of this paper is to present further flexibility through the risk aversion specification, within the context of non-expected utility, through relaxation of the iso-elasticity assumption. By allowing attitudes toward risk to reflect the information set used for the decision process, risk aversion is no longer fixed, but responds to the evolution in the state of the world as well as the distributional assumptions governing the state variables. The advantage is that the same individual may be a risk-lover over certain states and distributions, while being risk averse over others. The model is developed within a continuous-time setting for consumption and leverage choices. The closed form solution for the risk aversion function gives results that are appealing on intuitive grounds. In particular, risk aversion increases in the variance of the risky return, and falls in wealth and equity premium. Estimation results are presented.
Keywords: D81; D91; 330